The Interaction between Oxidative Stress Biomarkers and Gut Microbiota in the Antioxidant Effects of Extracts from Sonchus brachyotus DC. in Oxazolone-Induced Intestinal Oxidative Stress in Adult Zebrafish - Juan Yang; Wei-Wei Zhou; Dong-Dong Shi; Fang-Fang Pan; Wen-Wen Sun; Pei-Long Yang; Xiu-Mei Li (MDPI AG, 2023)
Oxidative stress is a phenomenon caused by an imbalance between the production and accumulation of reactive oxygen species in cells and tissues that eventually leads to the production of various diseases. Here, we investigated the antioxidant effects of the extract from Sonchus brachyotus DC. (SBE) based on the 0.2% oxazolone-induced intestinal oxidative stress model of zebrafish. Compared to the model group, the treatment group alleviated oxazolone-induced intestinal tissue damage and reduced the contents of malondialdehyde, reactive oxygen species, IL-1β, and TNF-α and then increased the contents of superoxide dismutase, glutathione peroxidase, and IL-10. The 16s rDNA gene sequencing findings demonstrated that SBE could increase the relative abundance of Fusobacteriota, Actinobacteriota, and Firmicutes and decrease the relative abundance of Proteobacteria. Based on the correlation analysis between the oxidative stress biomarkers and intestinal flora, we found that the trends of oxidative stress biomarkers were significantly correlated with intestinal microorganisms, especially at the genus level. The correlations of MDA, IL-1β, and TNF-α were significantly negative with Shewanella, while SOD, GSH-Px, and IL-10 were significantly positive with Cetobacterium, Gemmobacter, and Flavobacterium. Consequently, we concluded that the antioxidant effect of SBE was realized through the interaction between oxidative stress biomarkers and gut microbiota.